2006
DOI: 10.1038/sj.ejcn.1602426
|View full text |Cite
|
Sign up to set email alerts
|

Energy balance and physical activity in obese children attending day-care centres

Abstract: Objective: To evaluate energy balance and physical activity in obese preschool children attending day-care centres. Design: Cross-sectional study. Subjects: Twenty-four 3-5 years old obese children selected at random from four different day-care centres in Santiago City, Chile. Total energy expenditure (TEE) was measured by doubly labelled water and physical activity as recorded by TRITRAC R3D motion sensor. Energy intake was assessed by measuring food intake while at the centre, along with the recording of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 31 publications
1
35
1
1
Order By: Relevance
“…The research by Fairclough et al (2007) included physical education (PE) periods during the morning hours, and these PE periods were the most active time of the morning. The results of Vasquez et al (2006Vasquez et al ( :1117 are also to be expected, as toddlers have more free time for play during school hours than children who attend formal schooling. In our study the children did not have a formal PE period.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…The research by Fairclough et al (2007) included physical education (PE) periods during the morning hours, and these PE periods were the most active time of the morning. The results of Vasquez et al (2006Vasquez et al ( :1117 are also to be expected, as toddlers have more free time for play during school hours than children who attend formal schooling. In our study the children did not have a formal PE period.…”
Section: Discussionsupporting
confidence: 49%
“…Significant differences were also found in the TEE and the predetermined energy requirements for boys and girls. Energy input for children who were obese according to the National Center for Health and Statistics standard (WHO 1986) was already 5.4% higher in this study than the energy requirements (Vasquez et al 2006(Vasquez et al :1115. In a study on 8-yearold -16-year-old overweight and obese children Aires et al (2007:871) reported less activity over the weekend compared to that during the week, while similar findings were reported by Trost, McIver and Pate (2005:S531).…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…In Latin America, the focus had mainly been on establishing capacity to evaluate interventions designed to combat the double burden of malnutrition that exists in these areas (34)(35)(36) . O) in a technique known as the doublelabelled water method, researchers can obtain an estimate of total daily energy expenditure in individuals undergoing their normal daily living activities.…”
Section: Stable Isotopes Methods In Nutrition 497mentioning
confidence: 99%